2020
DOI: 10.32604/biocell.2020.09097
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination of colistin with imipenem, amikacine or ciprofloxacin against Acinetobacter baumannii and Pseudomonas aeruginosa carbapenem-resistant isolated in Annaba hospital Algeria

Abstract: Objective: The aim of this study is to detect in vitro the synergetic activity of colistin in combination with imipenem, amikacin or ciprofloxacin, at sub-inhibitory concentrations, against carbapenems-resistant (CR) Acinetobacter baumannii and Pseudomonas aeruginosa strains isolated from various wards in Annaba teaching hospital in eastern Algeria. Materials and Methods: The minimal inhibitory concentrations (MIC) were determined by broth macrodilution (BMD).Carbapenemase encoding genes were screened using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Little information is available on successful treatment regimens of A. baumannii by FQs combinations with antimicrobial or non-antimicrobial agents. Few attempts have been made so far to control the resistance of this strain [10,49]. Our results revealed that both doxycycline and colistin still retain good activities against A. baumannii.…”
Section: Plos Onementioning
confidence: 67%
“…Little information is available on successful treatment regimens of A. baumannii by FQs combinations with antimicrobial or non-antimicrobial agents. Few attempts have been made so far to control the resistance of this strain [10,49]. Our results revealed that both doxycycline and colistin still retain good activities against A. baumannii.…”
Section: Plos Onementioning
confidence: 67%
“…All of them were isolated from patients hospitalized in the various departments at Annaba Hospital, Algeria. Their identification and susceptibility profile are reported by Toumi et al [ 55 ] and Meliani et al [ 56 ]. Four standard drugs Imipenem, Ciprofloxacin, Amikacine, and fluconazole were used as positive controls, while DMSO was used as a negative control in this study.…”
Section: Methodsmentioning
confidence: 86%